2021
DOI: 10.3390/ma14237317
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Phase Field Model for Nanomaterials

Abstract: The lattice phase field model is developed to simulate microstructures of nanoscale materials. The grid spacing in simulation is rescaled and restricted to the lattice parameter of real materials. Two possible approaches are used to solve the phase field equations at the length scale of lattice parameter. Examples for lattice phase field modeling of complex nanostructures are presented to demonstrate the potential and capability of this model, including ferroelectric superlattice structure, ferromagnetic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Racetrack memory devices, 46) which are one-dimensional magnetic nanowire devices, has caused to consider the possibility of creating analogous ferroelectric devices by placing ferroelectric structures in a one-dimensional limit. Figure 5 shows the lattice phase-field simulation 42)…”
Section: -3mentioning
confidence: 99%
See 1 more Smart Citation
“…Racetrack memory devices, 46) which are one-dimensional magnetic nanowire devices, has caused to consider the possibility of creating analogous ferroelectric devices by placing ferroelectric structures in a one-dimensional limit. Figure 5 shows the lattice phase-field simulation 42)…”
Section: -3mentioning
confidence: 99%
“…Similar stable domain patterns were obtained by changing the initial random values or using a lattice phase-field model. 42) Because the interface-intermixing effect was considered in the simulation, we examined domain structures with one and no intermixing layers. The simulation results showed that interface intermixing did not significantly affect the polarization and domain structure.…”
mentioning
confidence: 99%
“…It was shown that micromagnetic simulations could predict the magnetic properties for FePt based exchange-coupled bit patterned media [ 22 , 23 , 24 , 25 , 26 , 27 ]; however, only a few works for core-shell shaped island composite were reported. It should be noted that the hysteresis loop of the core-shell island is very sensitive to the stacking structure of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the hysteresis loop of the core-shell island is very sensitive to the stacking structure of the composite. Our prior works [ 16 , 22 ] on double-layered exchange spring nanoislands demonstrated that the micromagnetic simulations could predict the magnetization hysteresis loop with domain structure evolution at a switching external field. Therefore, the main objective of this letter is to simulate various core-shell type ECC FePt/Fe structures with different core radii and shell thickness by micromagnetic simulation.…”
Section: Introductionmentioning
confidence: 99%